2023
DOI: 10.1088/1361-6641/acb9b6
|View full text |Cite
|
Sign up to set email alerts
|

Design of step-graded AlGaN buffers for GaN-on-Si heterostructures grown by MOCVD

Abstract: For the growth of low-defect crack-free GaN heterostructures on large-area silicon substrates, compositional grading of AlGaN is a widely adapted buffer technique to restrict the propagation of lattice-mismatch induced defects and balance the thermal expansion mismatch-induced tensile stress. So far, a consolidation of the design strategy of such step-graded buffers has been impaired by the incomplete understanding of the effect of individual buffer design parameters on the mechanical and microstructural prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…A schematic of the process flow is indicated in Figure while corresponding experimental results are shown in Figure . Figure a illustrates how the GaN solid immersion lenses are defined and suspended on a strain-optimized heteroepitaxially grown GaN-on-Si chip based on the wafer-scale compatible microfabrication process reported in earlier study . Initially, polymer resist lenses are defined by grayscale lithography and thermal reflow (1), followed by inductively coupled plasma (ICP) dry etching to transfer the lens shape into the 2 μm thick GaN top layer (2).…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…A schematic of the process flow is indicated in Figure while corresponding experimental results are shown in Figure . Figure a illustrates how the GaN solid immersion lenses are defined and suspended on a strain-optimized heteroepitaxially grown GaN-on-Si chip based on the wafer-scale compatible microfabrication process reported in earlier study . Initially, polymer resist lenses are defined by grayscale lithography and thermal reflow (1), followed by inductively coupled plasma (ICP) dry etching to transfer the lens shape into the 2 μm thick GaN top layer (2).…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…The heteroepitaxial growth on cost-effective Si(111) substrates is the preferred choice for power electronic devices; however, GaN-on-Si epitaxy is characterized by large mismatches in lattice parameter and thermal expansion coefficient. High defect densities and cracking of films exceeding 1 μm in thickness are related issues that still need to be solved in the epitaxy process. , A process window for high-quality growth of GaN/AlN by MSE has already been demonstrated. Careful design of buffer layers and strain management is necessary to successfully grow high-quality and crack-free GaN/AlN on Si. ,, The integration of an Al seed layer into the process flow has proven beneficial to improve the crystal quality of AlN-on-Si grown by various epitaxy technologies. Enhanced surface diffusion and avoiding the formation of SiN x layers promote the adhesion and subsequent growth of AlN layers. However, a thorough investigation of the impact of this seed layer on the film morphology, structural quality, and film polarity of sputtered GaN/AlN/Si(111) stacks has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 15 18 Careful design of buffer layers and strain management is necessary to successfully grow high-quality and crack-free GaN/AlN on Si. 8 , 14 , 19 The integration of an Al seed layer into the process flow has proven beneficial to improve the crystal quality of AlN-on-Si grown by various epitaxy technologies. Enhanced surface diffusion and avoiding the formation of SiN x layers promote the adhesion and subsequent growth of AlN layers.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [ 17 ] achieved the growth of 2 μm‐thick, crack‐free GaN thin films by introducing ultra‐thin AlN/GaN superlattice interlayers into the superlattices, they controlled the average Al content by varying the thickness of the superlattice AlN and GaN, and found that cracks could be suppressed more effectively if the optimal average Al content is less than 0.5. Ghosh et al [ 18 ] optimized MOCVD‐grown GaN/graded‐AlGaN/AlN/Si heterostructures by in‐situ curvature measurements, and they found that the GaN layer produces more compressive stress than the AlGaN buffer layer, and the underlying AlGaN layer determines the magnitude of this stress. Furthermore, when the buffer layer thickness is fixed, the average stress accumulated during GaN growth is related to its structural properties.…”
Section: Introductionmentioning
confidence: 99%